Digital ledger technology-based real estate transaction mechanism and its block size assessment. (20th August 2019) - Singh, Nikita; Vardhan, Manu
Distributed ledger technology (DLT) is set to transform the existing architectural models of financial institutions and government machineries. Although real estate transactions are a major source for the governments to earn revenue, these are plagued with the risk of fraudulent practices. The digital documents are vulnerable to the alteration or any other attacks or can be tampered and ownership of the documents can be changed. The centralised storage involves single point of failure as well as network traffic overhead. The proposed distributed and decentralised blockchain-based architecture provides protection against any intrusive activity which is offset by the majority voting achieved in consensus mechanism for each transaction and verification request. The proposed work provides web interface for user queries and analysis of query search time is carried out.